2003
DOI: 10.1034/j.1600-0420.2003.00085.x
|View full text |Cite
|
Sign up to set email alerts
|

Vigabatrin: longterm follow‐up of electrophysiology and visual field examinations

Abstract: ABSTRACT.Background: To report the results of repeated electrophysiological and visual field examinations in patients with vigabatrin-associated visual field loss (VGB-VFL) and the relationship between these electrophysiological findings, the cumulative dose of vigabatrin and the extent of visual field loss. Methods: Twenty-two eyes of 11 patients with VGB-VFL were studied. All patients underwent surgery for therapy-resistant epilepsy. Repeated electrooculograms (EOGs) and flash electroretinograms (ERGs) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 19 publications
3
19
0
Order By: Relevance
“…Similar reductions in cone b-wave amplitudes in the 30 Hz flicker ERG are also seen in rabbits receiving vigabatrin [14]. Several studies have demonstrated a reduced ERG also after discontinuation of medication [15,17,18,21]. Duboc et al [27] have performed a study in rats, tissue has been confirmed in another investigation by Sills et al [29].…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Similar reductions in cone b-wave amplitudes in the 30 Hz flicker ERG are also seen in rabbits receiving vigabatrin [14]. Several studies have demonstrated a reduced ERG also after discontinuation of medication [15,17,18,21]. Duboc et al [27] have performed a study in rats, tissue has been confirmed in another investigation by Sills et al [29].…”
Section: Discussionsupporting
confidence: 62%
“…Most of these studies have demonstrated neither improvement nor worsening 1-47 months after treatment was stopped, suggesting that the visual field defect is irreversible but not progressive [15][16][17][18][19][20][21]. In addition, some of these investigators have assessed ERGs, which showed irreversible changes [15,17,18,21]. The most consistent ERG results were a reduction in photoptic b-wave amplitude, a reduction in amplitudes of the oscillatory potentials and a reduction in amplitudes of the 30 Hz flicker ERG.…”
Section: Introductionmentioning
confidence: 99%
“…Quite a few studies have addressed the question whether these defects are reversible or not and most data support the hypothesis of permanent visual field constriction [12,14,15,[17][18][19][20][21][22]. The time of follow-up varies between the different studies spreading from 3 to 38 months.…”
Section: Introductionmentioning
confidence: 97%
“…VGB medication has been correlated to a reduction of rod b-wave amplitudes and cone b-wave amplitudes, as well as to a decline of amplitudes of oscillatory potentials (OPs), reflecting inner retinal function. The ff-ERG alterations are usually considered irreversible [19,22,23,25]. To date, there have been uncertainties concerning the role of the drug dose in VGB toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…The cause of the visual field defects is still not fully understood. Numerous studies have revealed alterations of full-field ERG (ff-ERG) responses [11,13,16,[18][19][20][21][22][23][24][25][26][27][28], suggesting retinal damage as the origin of visual field defects. VGB medication has been correlated to a reduction of rod b-wave amplitudes and cone b-wave amplitudes, as well as to a decline of amplitudes of oscillatory potentials (OPs), reflecting inner retinal function.…”
Section: Introductionmentioning
confidence: 99%